Clinical and histopathological characteristics of HIV-psoriasis cases (2019)
ABSTRACT: Psoriasis affects the individual, their social and family environment (1,2), comorbidity with human immunodeficiency virus (HIV) could worsen its clinical presentation, an underlying cause of this shame are dysregulation and immunosuppression (3). It has been postulated that gp120 HIV glycoprotein acts as superantigen that activate CD4+ cells, Bcells, and basophils, even it could stimulate expression HLA-DR in keratinocyte, a feasible mechanism for HIV to cause psoriasis in previously non-psoriatic individuals (3). The prevalence of psoriasis-HIV is between 2.5% to 5%. Psoriasis can be the initial cutaneous manifestation of an HIV infection, and it is present during all phases of disease including AIDS. Vulgar, guttate and erythrodermic psoriasis are most frequently associated with HIV (3). Objectives: To describe the clinical and histopathological characteristics